Characterization of micro‐mechanical properties of AlON ceramic by cantilever bending test. Issue 11 (17th June 2019) - Ding, Maomao; Robertson, Stuart; Wang, Tun; Fan, Lingcong; Sun, Zehan; Maerz, Benjamin; Crookes, Robert; Xie, Jianjun; Shi, Ying; Wu, Houzheng
Abstract: The AlON transparent ceramic cantilever beams containing twin and grain boundaries were fabricated by focused ion beam technique. The deformation behaviors were investigated by measurement of the load and displacement dependence of cantilever beams from micro bending tests. Young's modulus of AlON transparent ceramics was calculated from load and displacement curves, the results of which were consistent with results of previous works. Moreover, the bonding strengths of twin lamella boundary, twin boundary, and normal grain boundary in AlON transparent ceramics were 5.00, 5.05, and 4.81 GPa, respectively.